2000
DOI: 10.1103/physrevb.61.2711
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous polarization and piezoelectric field inGaN/Al0.15Ga

Abstract: We have investigated the effects of the built-in electric field in GaN/Al 0.15 Ga 0.85 N quantum wells by photoluminescence spectroscopy. The fundamental electron heavy-hole transition redshifts well below the GaN bulk gap for well widths larger than 3 nm for the specific quantum wells investigated and exhibits a concomitant reduction of the intensity with increasing well thickness. The experimental data are quantitatively explained by means of a self-consistent tight-binding model that includes screening ͑eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(108 citation statements)
references
References 15 publications
2
106
0
Order By: Relevance
“…7,[9][10][11] We have shown that SIA in GaN-based heterostructures results in a spin splitting of subbands in k space, which was later confirmed by magnetotransport measurements. [18][19][20][21] The Rashba spin splitting due to SIA, which is not expected in wide band semiconductors, in GaN/AlGaN heterostructures is caused by a large piezoelectric effect, 22 which yields a strong electric field at the GaN/AlGaN interface and a strong polarization induced doping effect. 23 Figures 5͑a͒ and 5͑b͒ demonstrate the dependences of the photocurrent on the angle p for positive angle 0 .…”
Section: Figmentioning
confidence: 99%
“…7,[9][10][11] We have shown that SIA in GaN-based heterostructures results in a spin splitting of subbands in k space, which was later confirmed by magnetotransport measurements. [18][19][20][21] The Rashba spin splitting due to SIA, which is not expected in wide band semiconductors, in GaN/AlGaN heterostructures is caused by a large piezoelectric effect, 22 which yields a strong electric field at the GaN/AlGaN interface and a strong polarization induced doping effect. 23 Figures 5͑a͒ and 5͑b͒ demonstrate the dependences of the photocurrent on the angle p for positive angle 0 .…”
Section: Figmentioning
confidence: 99%
“…We took into account the screening of electric field by photoexcited carriers 21 whose number was estimated from the laser excitation power density after assuming that square recombination of carriers predominates. 22 The results of these theoretical estimations are shown in Fig.…”
mentioning
confidence: 99%
“…The e1-hh1 transition energies were calculated by using Eq. (1) [21] in which the red shift of the emission wavelength due to polarization-induced electric fields for as-grown and additional built-in field for detector devices in the quantum well were taken into account. …”
Section: Resultsmentioning
confidence: 99%